2016
DOI: 10.1186/s12917-017-0953-3
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors of different hemoplasma species infections in cats

Abstract: BackgroundHemoplasma species (spp.) commonly cause infections in cats worldwide. However, data on risk factors for infections are limited. The aim of this study was to determine the prevalence of hemoplasma spp. infections in cats in Southern Germany and to assess risk factors associated with infection.ResultsDNA was extracted from blood samples of 479 cats presented to different veterinary hospitals for various reasons. DNA of feline hemoplasmas was amplified by use of a previously reported PCR assay. Direct … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
31
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 25 publications
6
31
3
Order By: Relevance
“…This supports the hypotheses of horizontal transmission during aggressive interactions between cats and transmission through arthropod vectors, respectively (64). In Germany, between 7.2% and 22.5% of cats are infected, and the most common species is Mhm (6,11,47,63). Ccats from multi-cat households were significantly more likely to be infected with a haemotropic Mycoplasma spp., with shelter cats having similar infection rates as cats from private multi-cat homes.…”
Section: Haemotropic Mycoplasma Spp Infectionssupporting
confidence: 79%
See 1 more Smart Citation
“…This supports the hypotheses of horizontal transmission during aggressive interactions between cats and transmission through arthropod vectors, respectively (64). In Germany, between 7.2% and 22.5% of cats are infected, and the most common species is Mhm (6,11,47,63). Ccats from multi-cat households were significantly more likely to be infected with a haemotropic Mycoplasma spp., with shelter cats having similar infection rates as cats from private multi-cat homes.…”
Section: Haemotropic Mycoplasma Spp Infectionssupporting
confidence: 79%
“…Strict flea control should be maintained (e.g., with imidacloprid) as this has been shown to stop transmission of B. henselae (15). (11,81). Most commonly, haemotropic Mycoplasma spp.…”
Section: Bartonella Spp Infectionsmentioning
confidence: 99%
“…The significant association between hemoplasma infection and the co-infection with retrovirus (FeLV/FIV) shown by this and previous studies [6,19,25,35,39] could be explained by the well-known immunosuppressive effect of these retroviruses. However, since FIV is mainly transmitted through bite wounds, it has been suggested that the strong statistical association between this retroviral infection and feline hemoplasmosis could be supporting the horizontal route of transmission [20].…”
Section: Discussionsupporting
confidence: 60%
“…It has been frequently reported that there is an association between the age of the cats and hemoplasma infection. Some studies have described that adult age could be a risk factor for these infections [7,11,23,26,33,35,40,41]. In our study, being an adult cat (> one year-old) was statistically associated with hemoplasma infection.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation